2010
DOI: 10.1088/0953-8984/23/1/015402
|View full text |Cite
|
Sign up to set email alerts
|

Phonons in graphene with point defects

Abstract: The phonon density of states (DOS) of graphene with different types of point defects (carbon isotopes, substitution atoms, vacancies) is considered. Using a solvable model which is based on the harmonic approximation and the assumption that the elastic forces act only between nearest neighboring ions we calculate corrections to the graphene DOS dependent on the type and concentration of defects. In particular the correction due to isotopic dimers is determined. It is shown that a relatively small concentration… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 40 publications
(90 reference statements)
0
33
0
Order By: Relevance
“…24 Several ways to reduce the thermal conductivity have already been examined, such as interface mismatching between graphene and nanoribbons, 25,26 the presence of isotopes, [27][28][29][30] cross-plane phonon coupling in a few layers of graphene, 31 strain, 32 random hydrogen vacancies in graphene, 33 and point defects. [34][35][36] Edge disorder has been predicted theoretically to suppress heat conductance of graphene nanoribbons, [37][38][39] and ZT exceeding 3 has been theoretically predicted for such systems in the diffusive limit. 40 GALs have been proposed as a flexible platform for creating a semiconducting material with a band gap which can be tuned by varying the antidot size, shape, or lattice symmetry.…”
Section: Introductionmentioning
confidence: 97%
“…24 Several ways to reduce the thermal conductivity have already been examined, such as interface mismatching between graphene and nanoribbons, 25,26 the presence of isotopes, [27][28][29][30] cross-plane phonon coupling in a few layers of graphene, 31 strain, 32 random hydrogen vacancies in graphene, 33 and point defects. [34][35][36] Edge disorder has been predicted theoretically to suppress heat conductance of graphene nanoribbons, [37][38][39] and ZT exceeding 3 has been theoretically predicted for such systems in the diffusive limit. 40 GALs have been proposed as a flexible platform for creating a semiconducting material with a band gap which can be tuned by varying the antidot size, shape, or lattice symmetry.…”
Section: Introductionmentioning
confidence: 97%
“…Both calculation models predict that the additional peaks arise at the same frequencies, K 1-2 and K 4-5 . These additional peaks accompany the splitting of the intersected modes, which is analogous to the bandgap opening in the doped graphene [43,45]. It has been suggested that the shapes of the additional peaks are the result of optical phonons that occupy a narrow band with relatively low phonon group velocity [45].…”
Section: Resultsmentioning
confidence: 95%
“…The most remarkable change in the DOS distribution is that the increased concentration rate reduces or broadens all of the M point peaks of the pure sheet. In Adamyan's calculations [43] for sheets doped with aluminum atoms, which have a mass comparable to silicon atoms, the peaks are lower near the van Hove singularities. Generally, peak broadening indicates that the scattering rates increase [33,44] for all phonons.…”
Section: Resultsmentioning
confidence: 96%
“…However, in graphene the atomic interactions are determined by covalent forces. These forces cause the stiffness of the planes with respect to the transverse short-range displacements of atoms [1]. In accordance with the Mermin-Wagner theorem [39] the plane of graphene remains unstable with respect to longrange transverse distortions, resulting in the appearance of ripples [12,40].…”
Section: Graphene: Out-of-plane Vibrationsmentioning
confidence: 84%
“…The distances between an atom and three neighboring atoms equal In the pair potential approximation the potential energy of the vibrations of atoms depends on the distances R n = r n -a (explicit form of this energy in harmonic approximation, see e.g. in [1]). The expansion of these distances over the displacements x n , y n and z n depends on the powers R m = (bx + cy + (x 2 + y 2 + z 2 )/a) m (here the subscript n is omitted for simplicity).…”
Section: Graphene: Out-of-plane Vibrationsmentioning
confidence: 99%